Palatabilne zdravilne oblike za zdravljenje psov in mačk - Kristan, Katja (Farmacevtski vestnik, 2014)
Dogs and cats are our companions and administration of oral medicines to sick animals represents one of the biggest challanges, especially for chronically administered medications. There is an increased need for palatable dosage forms, which are voluntarily accepted by the animal, either from the outstretched hand of the pet owner or from a feeding bowl. This review focuseson gastrointestinal physiology and describes taste and flavour preferences of dogs and cats in the context of applying these principles to the development of palatable drugs for companion animals. Challenges in palatability testing and selection of the appropriate pharmaceutical dosage form for dogs and cats are also presented.
Keywords: cats; dogs; drug; mačke; palatability; palatabilnost; psi; veterinarska medicina; veterinary medicine; zdravila